2020
DOI: 10.21203/rs.3.rs-18600/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Survival Time to Recovery from COVID-19: A Case Study on Singapore

Abstract: Background Novel coronavirus (COVID-19) is a new strain of viruses that originated in China. In December 2019, a strange case of pneumonia was reported in Wuhan, which then was diagnosed to be COVID-19. In Singapore, the first positive case was reported on January 23, 2020. Aim This study aims to study the recovery time from COVID-19 in Singapore between January 23 and March 13, 2020. Methods It's a retrospective study from January 23 until March 13, 2020 for 187 cases with COVID-19 infection. Data of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
4
4
0
Order By: Relevance
“…Cox regression model showed that younger patients recover faster compared to elderly patients. Similar ndings were also reported in literature (28,29). In fact, many studies found a high proportion of severe cases and fatality rate among elderly patients with COVID-19 (16,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 90%
“…Cox regression model showed that younger patients recover faster compared to elderly patients. Similar ndings were also reported in literature (28,29). In fact, many studies found a high proportion of severe cases and fatality rate among elderly patients with COVID-19 (16,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 90%
“…Cox regression model showed that younger patients recover faster compared to elderly patients. Similar ndings were also reported in literature (28,29). In fact, many studies found a high proportion of severe cases and fatality rate among elderly patients with COVID-19 (16,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 89%
“…Cox regression model showed that younger patients recover faster compared to elderly patients. Similar ndings were also reported in literature (28,29). In fact, many studies found a high proportion of severe cases and fatality rate among elderly patients with COVID-19 (16,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 88%